PERAN KEMENTERIAN AGAMA KABUPATEN BIMA DALAM MENENTUKAN STANDAR DAN VALIDASI ARAH KIBLAT DI KECAMATAN LAMBU KABUPATEN BIMA - Ma’rif, Imam; Amin , Muhammadiyah (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract The main problem in this study is how the role of the Ministry of Religion of Bima Regency in determining standards and validating the direction of the qibla in Lambu District, Bima Regency. From the main problem, it is divided into 2 (two) problem formulations, namely 1) How is the function of the Ministry of Religion of Bima Regency in determining or validating the direction of the qibla in Lambu District, 2) How are the obstacles and challenges faced by the Ministry of Religion of Bima Regency in the process of validating the direction of the qibla in Lambu District. The type of research used is a qualitative approach with a descriptive type of field research. Data was collected through, observation, interviews and documentation with information from the Ministry of Religion of Bima Regency, the Religious Affairs Office of Lambu District, and mosque or prayer room administrators. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that, 1) the role of the Ministry of Religion in validating the direction of the qibla needs to be strengthened through increased socialization and an active approach to the community, considering that there is still a low demand for measurement and trust in the doctrinal method. 2) It is necessary to improve the quality of human resources and provide more adequate facilities and infrastructure to overcome technical obstacles in the field. This research implies the need to increase public awareness of the importance of determining the direction of the qibla scientifically and strengthening the proactive role of the Ministry of Religion of Bima Regency through socialization, mentoring, capacity building of human resources in the field of astronomy, and the provision of supporting facilities for measuring the direction of the qibla Keywords: Qibla Direction, Role of the Ministry of Religion, Standards and Validation.